2019
DOI: 10.1007/s10443-019-09784-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Fastener Pull-out Response in Composite Joints under Static and Dynamic Loading Rates

Abstract: A novel device is adopted in order to experimentally investigate the effect of various loading rates on the pull-out response of a fastened composite joint configuration. The joint coupons comprise a composite plate made of the carbon/epoxy AS4/8552 material system and a centrally located titanium lockbolt. Tensile-type (pull) loading was applied to the specimens in a velocity range from quasi-static to 2.1 m/s. Both quasi-static and dynamic tests were conducted using the same specimen geometry and boundary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Heimbs et al's study suggested that while single-lap shear with one bolt showed little to no rate dependence [230], a single lap shear with two bolts did show increased strength and energy absorption at 10m/s due to a change in failure mode from net tension to "extensive bearing and pull-through failure". Another study also noted a change in damage mode between quasistatic and 2m/s loading [231], but while they found that the failure stress increased, the absorbed energy decreased (presumably due to rate-dependent stiffening).…”
Section: Jointsmentioning
confidence: 97%
“…Heimbs et al's study suggested that while single-lap shear with one bolt showed little to no rate dependence [230], a single lap shear with two bolts did show increased strength and energy absorption at 10m/s due to a change in failure mode from net tension to "extensive bearing and pull-through failure". Another study also noted a change in damage mode between quasistatic and 2m/s loading [231], but while they found that the failure stress increased, the absorbed energy decreased (presumably due to rate-dependent stiffening).…”
Section: Jointsmentioning
confidence: 97%